MAGNETIC RESONANCE IMAGING FEATURES OF INTRAVENTRICULAR EPENDYMOMAS IN Five CATS - DeJesus, Antonia (Vet Radiol Ultrasound, 2016)
Intraventricular ependymoma is a rare type of feline intracranial neoplasia and published information on magnetic resonance imaging (MRI) characteristics is currently lacking. The purpose of this retrospective case series study was to describe the clinical and MRI characteristics of histopathologically confirmed intraventricular ependymomas in a group of cats. Five cats met inclusion criteria. In relation to normal gray matter, ependymomas appeared hyperintense on T2W, T2W‐FLAIR, PD, and DW‐EPI images; isointense on ADC images; and had subtle to strong contrast enhancement. Some variability was seen on T2*GRE and on T1W images with masses being isointense to hyperintense. Four ependymomas were small and homogeneous, and one was centrally cavitated. All cats had obstructive hydrocephalus, transtentorial herniation, and foramen magnum herniation. Perilesional edema was identified in most cats but was questionable in one. Intraventricular ependymoma should be considered as a differential diagnosis for cats with this combination of MRI signs.